The Effect of Using a Traditional Mask of Moringa Leaves for Dry Facial Skin Care - Meilinda, Fuji Rahma; Astuti, Murni (International Journal of Natural Science and Engineering, 2023)
Dry facial skin can be caused by several factors including age, sun exposure, weather, genetics, skin structure, diet, environmental factors, and skin diseases. The purpose of this study was to determine the effect of using traditional Moringa leaf masks for dry facial skin care. This type of research is experimental research with quasi-experimental methods. The research sample consisted of 6 samples using the purposive sampling method. The type of data used is primary data. Data analysis used the normality test, homogeneity test, and hypothesis testing (ANOVA), followed by the Duncan test. Analysis of normality and homogeneity of the data is used to test prerequisite analysis before testing the hypothesis. The results showed that in the control group (X0) without the use of traditional moringa leaf masks, there was no change in the level of skin moisture and the level of smoothness of facial skin texture. In the experimental group X1 and X2 using a traditional leaf mask showed a significant change in the level of moisture and smoothness of facial skin texture. There are differences in the effect of treating dry faces on women aged 35-45 years using traditional masks from Moringa leaves in three different treatments for indicators of moisture and facial skin texture with a significance of 0.016 <0.050.